DIAGNOSTIC VALUE OF SIMULTANEOUS MEASUREMENT OF PROCALCITONIN, INTERLEUKIN-6 AND HS CRP IN PREDICTION OF EARLY-ONSET NEONATAL SEPSIS - alireza abdollahi; saeed shoar; fatemeh nayyeri; mamak shariat (Mediterranean Journal of Hematology and Infectious Diseases)
Neonatal sepsis is a major cause of morbidities and mortalities mostly remarkable in the third world nations .We aimed to assess the value of simultaneous measurement of procalcitonin (PCT) and interleukin-6 (IL-6) in association with high sensitive- C reactive protein in prediction of early neonatal sepsis.